Faktor yang Mempengaruhi Keputusan Investor Dalam Membeli Saham di Perusahaan Sektor Perkebunan Selama Pandemi Covid 19 - HRP, Husaini Muhammad (Universitas Tabanan, 2023)
“while the Covid-19 pandemic hit, stock fees plummeted, making traders cautious whilst making stock funding decisions. The reason of this examine is to take a look at whether a business enterprise's profitability, its liquidity and its market fee have an effect on the stock costs of groups within the forest plantation zone. traded and presented for sale on the Indonesian inventory market. to the public. stock trade (IDX) for the length 2020-2021. in this take a look at, it has a dating with the signaling theory, the signaling concept that if a organization has properly monetary performance, there may be an effect at the inventory fee, at which the enterprise offers a signal. or records for investors to invest thru financial performance facts. This studies method makes use of a quantitative studies technique that has been examined by classical hypothesis checking out and a couple of linear regression assessments, displaying that profitability has an impact on stock prices, not among liquidity and marketplace cost. now not in the stock charges of plantation companies.”